2021
DOI: 10.1111/hsc.13415
|View full text |Cite
|
Sign up to set email alerts
|

Non‐skilled occupation as a risk factor of diabetes among working population: A population‐based study of community‐dwelling adults in Hong Kong

Abstract: Diabetes among working population brings to society concerns on productivity and social welfare cost, in addition to healthcare burden. While lower socio-economic status has been recognised as a risk factor of diabetes; occupation, compared with other socio-economic status indicators (e.g., education and income), has received less attention. There is some evidence from studies conducted in Europe that occupation is associated with diabetes risk, but less is known in Asia, which has different organisational cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…Similar to our findings, a review determined that people with white-collar jobs had a higher risk of type 2 DM [ 24 ]. But, in contrast to our findings, some researchers reported a greater risk of DM with non-skilled workers in Asia [ 25 ]. The disparity may be due to differences in work ethics and culture.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our findings, a review determined that people with white-collar jobs had a higher risk of type 2 DM [ 24 ]. But, in contrast to our findings, some researchers reported a greater risk of DM with non-skilled workers in Asia [ 25 ]. The disparity may be due to differences in work ethics and culture.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, previous research confirmed reasonable sensitivity and specificity of self-reported physician-diagnosed diabetes obtained via health interview surveys to assess social inequalities in prevalence of diabetes [47]. Secondly, although educational attainment and household income are generally deemed as the conventional socioeconomic indicators, they may not fully capture the health impact of other dimensions of socioeconomic disadvantage such as occupation [48,49], housing [50] and material and social deprivation [41,42]. The potential underreporting of income level in surveys may also introduce bias to the nonsignificant association of household income with diabetes prevalence observed in this study.…”
Section: Strengths and Limitationsmentioning
confidence: 82%